Pengaruh Perceived Organizational Support dan Psychological Empowerment terhadap Job Performance yang Dimediasi oleh Organizational Citizenship Behavior pada Kyriad Muraya Hotel - Amri; Rida Raihati Miska (Jurnal Manajemen Rekayasa dan Inovasi Bisnis, 2024)
The sample includes all employees at the Kyriad Muraya Hotel, totaling 110 uses the Structural Equation Modeling (SEM) method. The research results show that there is a positive and significant influence of Perceived Organizational Support and Organizational Citizenship Behavior on Job Performance. There is a positive and significant influence of Perceived Organizational Support and Psychological Empowerment on Organizational Citizenship Behavior. There is a positive and significant influence of Perceived Organizational Support on Job Performance which is mediated by the Organizational Citizenship Behavior variable. And there is a positive and significant influence of Psychological Empowerment on Job Performance which is mediated by the Organizational Citizenship Behavior variable. Sampel penelitian ini seluruh karyawan Hotel Kyriad Muraya yang berjumlah 110 orang dengan metode SEM. Hasil penelitian menunjukkan bahwa terdapat pengaruh positif dan signifikan Perceived Organizational Support dan Organizational Citizenship Behavior terhadap Job Performance. Terdapat pengaruh positif dan signifikan Perceived Organizational Support dan Psychological Empowerment terhadap Organizational Citizenship Behavior. Terdapat pengaruh positif dan signifikan Perceived Organizational Support terhadap Job Performance dimediasi oleh variabel Organizational Citizenship Behavior. Terdapat pengaruh positif dan signifikan Psychological Empowerment terhadap Job Performance dimediasi oleh Organizational Citizenship Behavior.